EFEITO DA APLICAÇÃO DE PIRIDOXINA E NIACINA NA CULTURA DA SOJA - TENÓRIO, João Pedro Barreto; MEIRA, Leonardo Borges Vasconcelos; VENDRUSCOLO, Eduardo Pradi; BORTOLHEIRO, Fernanda Pacheco de Almeida Prado (ANAIS DO ENIC, 2025)
-